Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Menggunakan Metode Hidrotermal Dengan Variasi Temperatur Reaksi - Yunus Olivia Novanto; Yelmida Azis; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Coral reefs that have been damaged so far are not utilized and only pollute the coast. Even though coral reefs are composed of calcium carbonate compounds which can be used for the synthesis of hydroxyapatite, an important mineral found in human bones. The purpose of this study was to synthesize HAp from precipitated calcium carbonate (PCC) coral reef using the hydrothermal method, determine the effect of temperature on the characteristics of HAp and determine the best temperature for making HAp using the hydrothermal method. Coral PCC and (NH4)2HPO4 were reacted with an initial Ca/P ratio of 1,77 and the reaction temperature varied from 110oC, 120oC, 130oC, 140oC, 150oC, 160oC and 170oC for 14 hours. Then the crude HAp was washed using distilled water to pH 7 and dried at 110oC. The synthesized hydroxyapatite was then analyzed using X-ray Diffraction (XRD) and Scanning Electron Microscopy-Electron Dispersive X-ray (SEM-EDX). The results of the XRD analysis showed that the diffractogram peak of the synthesized HAp was similar to the standard with the best crystallinity of 82,28% at 140oC, while the smallest crystal size was 19,5 nm at 170oC. For the results of SEM-EDX analysis, the synthesized HAp has a uniform particle size with the final ratio of Ca/P at 140oC is 1,76 and at 170oC is 1,96. Based on those analysis, the hydroxyapatite synthesized from PCC coral using the hydrothermal method has the best characteristics at the reaction temperature of 140oC and has met the ISO 13779-2-2008 standard as a bone impant.Keywords: coral, hydroxyapatite, hydrothermal, PCC, temperature.